(untitled) (Research, Society and Development, 2020)
The aim of this study was to identify the contributions of governance in the performance of Community Institutions of Higher Education (ICES) Unijuí and Univates. The study was carried out using the paradigmatic interpretative orientation of social reality, classified as a social research with an applied purpose, through the levels of exploratory and descriptive study, with a qualitative approach. The technical procedures used were bibliographic research, multi-case study, documentary and field research. Data were collected through semi-structured interviews and data analysis was performed using the Direct Research method. The results showed that in ICES the number of students does not necessarily reflect a positive and growing economic and financial performance. Therefore, it is understood that the more qualified, engaged, restructured and preceded by planning, the members of the governance structure are, the better the results obtained. It was observed that the values and dimensions of governance were present in the analyzed periods. The institutional actors, members of the governance structure, have demonstrated improvement in management over the years, providing competitive advantage. At Unijuí, four periods of strategic changes and adaptations were identified, and at Univates three periods. Although the empirical study focuses on two specific organizations, it is reasonable to assume that this scenario, due to isomorphic factors, largely reflects the functioning dynamics of the gaucho community system of secular higher education.